An experimental and theoretical NMR study of NH-benzimidazoles in solution and in the solid state: proton transfer and tautomerism - Nieto, Carla I.; Cabildo, Pilar; García, M. Ángeles; Claramunt, Rosa M.; Alkorta, Ibon; Elguero, José (Beilstein Journal of Organic Chemistry, 2014)
This paper reports the 1H, 13C and 15N NMR experimental study of five benzimidazoles in solution and in the solid state (13C and 15N CPMAS NMR) as well as the theoretically calculated (GIAO/DFT) chemical shifts. We have assigned unambiguously the "tautomeric positions" (C3a/C7a, C4/C7 and C5/C6) of NH-benzimidazoles that, in some solvents and in the solid state, appear different (blocked tautomerism). In the case of 1H-benzimidazole itself we have measured the prototropic rate in HMPA-d18.
Keywords: CPMAS; DNMR; GIAO; proton transfer; tautomerism